Cytoprotective Effects of Water Soluble Dihydropyrimidinthione Derivative Against UV-B Induced Human Corneal Epithelial Cell Photodamage - Du, Enming; Pu, Guojuan; He, Siyu; Qin, Fangyuan; Wang, Yange; Wang, Gang; Song, Zongming; Zhang, Junjie; Tao, Ye (Frontiers in Pharmacology, 2021)
Excessive UV-B exposure is well known to be a risk factor for corneal phototoxicity including direct DNA damage and disturbances in the antioxidant balance. Here, we showed a successful synthesis of a water-soluble and biocompatible small molecule DHPM 1 with dihydropyrimidinthione skeleton, which could effectively protect human corneal epithelial (HCE-2) cells from UV-B damage. In separate experiments, DHPM 1 absorbed UV-B rays and exhibited scavenging activity against intracellular ROS induced by UV-B radiation, thereby reducing the levels of DNA fragmentation. Additionally, UV-B exposure increased the expression of cleaved caspase-3, as well as the ratio of Bax to Bcl-2 at protein levels, while pretreatment with DHPM 1 significantly reversed these changes. To the best of our knowledge, this is the first report of a study based on dihydropyrimidinthione derivatives to develop a promising eye drops, which may well find extensive applications in UV-B caused corneal damage.